Bimbingan Konseling Dengan Metode Dzikir Untuk Mengatasi Depresi Pada Narapidana Wanita Kasus Penyalahgunaan Narkoba Dilapas Kelas II A Banyuwangi - Harfiyah, Nur Alif; Yohandi; Sulaiman, A. Husam (Jurnal Ilmu Bimbingan dan Konseling, 2025)
This study aims to describe the implementation process and impact of dhikr-based counseling for female inmates involved in drug abuse at the Class IIA Women’s Correctional Facility in Banyuwangi. The research stems from the high vulnerability to depression among female inmates, influenced by psychological stress, past trauma, and restrictive prison conditions. Using a qualitative phenomenological approach, this study investigates inmates’ inner experiences and their interpretation of the spiritual counseling program they participated in. Data were collected through in-depth interviews, observations, and ducumentation, then analyzed and validated using triangulation techniques. The findings show that dhikr practices conducted in both group and individual sessions positively influence emotional, cognitive, and spiritual aspects. Inmates reported increased calmness, improved cognitive restructuring, and better emotional regulation. Furthermore, the dhikr intervention strengthened regilious meaning and self-control, contributing to reduced depressive symptoms. Overall, dzikr-based counseling is proven effictive as a rehabilitative approach to support the mental recovery of female inmates within correctional institutions.